2020
DOI: 10.1007/s13258-020-01018-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oxidative stress induced-cytotoxicity by coptisine in V79-4 Chinese hamster lung fibroblasts through the induction of Nrf-2 mediated HO-1 expression

Abstract: Background Coptisine is a natural alkaloid compound and is known to have multiple beneficial effects including antioxidant activity. However, whether it can protect lung fibroblasts from oxidative damage has not been studied yet. Objectives To investigate the potential inhibitory effect of coptisine against oxidative stress in V79-4 lung fibroblast cells. Methods V79-4 cells were treated with H 2 O 2 (1 mM) in the presence or absence of coptisine (50 µg/ml), N-acetyl cysteine (NAC, 10 mM) or zinc protoporphyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As a homodimer, NQO1 needs to catalyze the reduction of quinone and semiquinone to stabilize hydroquinone and requires nicotinamide adenine dinucleotide or NADPH (58). Jo et al found that coptisine could reduce oxidative stress damage in Chinese hamster lung fibroblasts (59). With the increase of Nrf2 protein expression and nuclear translocation, the antioxidant protein expression of HO-1 regulated by Nrf2 was significantly increased (60).…”
Section: Discussionmentioning
confidence: 99%
“…As a homodimer, NQO1 needs to catalyze the reduction of quinone and semiquinone to stabilize hydroquinone and requires nicotinamide adenine dinucleotide or NADPH (58). Jo et al found that coptisine could reduce oxidative stress damage in Chinese hamster lung fibroblasts (59). With the increase of Nrf2 protein expression and nuclear translocation, the antioxidant protein expression of HO-1 regulated by Nrf2 was significantly increased (60).…”
Section: Discussionmentioning
confidence: 99%
“…But the results of previous studies indicated their differential functions. Coptisine, an antioxidant [ 37 ], could induce autophagy to exert anti-cancer effects [ 38 ]. No references indicated the anti-inflammatory activity of coptisine.…”
Section: Discussionmentioning
confidence: 99%
“…After stopping the reaction of the sample at 4°C, the amount of bilirubin produced was measured from the difference in optical density obtained at 460 and 530 nm using a microplate reader. HO-1 activity was presented as picomoles of bilirubin/mg protein as described in a previous study ( Jo et al, 2021 ).…”
Section: Materials and Methdsmentioning
confidence: 99%